Enhanced Activity of Hierarchical Nanostructural Birnessite-MnO(2)-Based Materials Deposited onto Nickel Foam for Efficient Supercapacitor Electrodes - Hung, Shang-Chao (Nanomaterials (Basel), 2020)
Hierarchical porous birnessite-MnO(2)-based nanostructure composite materials were prepared on a nickel foam substrate by a successive ionic layer adsorption and reaction method (SILAR). Following composition with reduced graphene oxide (rGO) and multiwall carbon nanotubes (MWCNTs), the as-obtained MnO(2), MnO(2)/rGO and MnO(2)/rGO-MWCNT materials exhibited pore size distributions of 2–8 nm, 5–15 nm and 2–75 nm, respectively. For the MnO(2)/rGO-MWCNT material in particular, the addition of MWCNT and rGO enhanced the superb distribution of micropores, mesopores and macropores and greatly improved the electrochemical performance. The as-obtained MnO(2)/rGO-MWCNT/NF electrode showed a specific capacitance that reached as high as 416 F·g(−1) at 1 A·g(−1) in 1 M Na(2)SO(4) aqueous electrolyte and also an excellent rate capability and high cycling stability, with a capacitance retention of 85.6% after 10,000 cycles. Electrochemical impedance spectroscopy (EIS) analyses showed a low resistance charge transfer resistance for the as-prepared MnO(2)/rGO-MWCNT/NF nanostructures. Therefore, MnO(2)/rGO-MWCNT/NF composites were successfully synthesized and displayed enhanced electrochemical performance as potential electrode materials for supercapacitors.